MODEL PELESTARIAN FUNGSI LINGKUNGAN PERKOTAAN BERBASIS EKOSANITA-IPLT (Studi kasus Kota Majalaya di DAS Citarum Hulu) - Pamekas, Pamekas (Jurnal Pendidikan Geografi Gea, 2007)
Effort to maintained the sustainability of the assimilative as well as carrying capacity of the human environment for medium and small town had already been done since the third of the fifth national development plan. About 2 700 unit of faecal sludge treatment plant had been constructed to improve the Indonesia city wastewater management. However, this effort have not meet the requirement while the economic crisis had placed water and sanitation sector in critical state. This research uses a system dynamics approach to model the ideal effort (EkoSanita- IPLT model) for improving wastewater management using the case of Majalaya town. The model is than used to study their behavior to formulate ways to maintained the assimilative capacity of drinking watersources and demonstrate their usefulness for policy formulation. The results indicate that increasing service coverage will decrease the wastewater volume in the water environment leading to increase the water environmental assimilative capacity. Extending service areas from one district to four and six district town leading to increase wastewater volume in the receiving body and subsequently reducing the assimilative capacity of the river body. The analysis also indicates that the existing capacity of faecal sludge treatment plant need to be extended. Finally, the EcoSanita-IPLT model has demonstrated their capability to formulate the policy for improving the wastewater management for the town of Majalaya in a comprehensive and systemic ways.Â Key word: Faecal sludge, system dynamic, policy formulation.